COMBO-FISH enables high precision localization microscopy as a prerequisite for nanostructure analysis of genome loci - Müller, Patrick; Schmitt, Eberhard; Jacob, Anette; Hoheisel, Jörg D.; Kaufmann, Rainer; Cremer, Christoph; Hausmann, Michael (International journal of molecular sciences, 2010)
With the completeness of genome databases, it has become possible to develop a novel FISH (Fluorescence in Situ Hybridization) technique called COMBO-FISH (COMBinatorial Oligo FISH). In contrast to other FISH techniques, COMBO-FISH makes use of a bioinformatics approach for probe set design. By means of computer genome database searching, several oligonucleotide stretches of typical lengths of 15-30 nucleotides are selected in such a way that all uniquely colocalize at the given genome target. The probes applied here were Peptide Nucleic Acids (PNAs)—synthetic DNA analogues with a neutral backbone—which were synthesized under high purity conditions. For a probe repetitively highlighted in centromere 9, PNAs labeled with different dyes were tested, among which Alexa 488Ò showed reversible photobleaching (blinking between dark and bright state) a prerequisite for the application of SPDM (Spectral Precision Distance/Position Determination Microscopy) a novel technique of high resolution fluorescence localization microscopy. Although COMBO-FISH labeled cell nuclei under SPDM conditions sometimes revealed fluorescent background, the specific locus was clearly discriminated by the signal intensity and the resulting localization accuracy in the range of 10-20 nm for a detected oligonucleotide stretch. The results indicate that COMBO-FISH probes with blinking dyes are well suited for SPDM, which will open new perspectives on molecular nanostructural analysis of the genome.
Gesehen am 10.05.2023
This article belongs to the Special Issue "Biomarkers"